A SURVEY ON THE IMPORTANCE AND IMPACT OF THE INTERNET ON LIFE-LONG EDUCATION: IMPLICATION FOR EDUCATIONAL DEVELOPMENT - Agoi, Moses Adeolu; Sain, Zohaib Hassan; Oshinowo, Oluwakemi Racheal; Agoi, Oluwanifemi Opeyemi (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
The rapid evolution of digital technology has significantly transformed the education landscape, mainly through integrating the internet. This shift has enhanced pedagogical activities in life-long education, making them more effective and engaging while ensuring widespread accessibility to learning resources. The availability of free online content has enabled users to communicate, share ideas, and acquire new skills seamlessly. The internet, a global system of interconnected computer networks, has become an indispensable tool in this digital age, opening vast knowledge reservoirs for teachers and students. This study investigates the internet's importance and impact on education, aiming to evaluate its role in improving educational practices and lifelong learning. An empirical approach was adopted, utilizing a structured questionnaire distributed among 100 students in two higher learning institutions. The findings revealed that the internet enhances academic performance, fosters critical thinking, encourages collaboration, and promotes independent learning. Furthermore, it highlighted the significant role of internet technology in democratizing education by providing accessible and affordable learning opportunities. In conclusion, the incorporation of internet technology has positively influenced the quality of the pedagogical process, thereby supporting the development and sustainability of lifelong education. These results underscore the internet's transformative potential in fostering educational advancement in the 21st century.